Cellulose nanocrystals for crop protection: leaf adhesion and controlled delivery of bioactive molecules. Issue 7 (22nd March 2023) - Ning, Like; You, Chaoqun; Jia, Yuxin; Chen, Jingqian; Zhang, Yu; Li, Xun; Rojas, Orlando J.; Wang, Fei
Abstract : TA/Cu-XCM@βCNC nanocarrier is developed for crop protection, the introduced system enables pH-responsive controlled delivery, enhances deposition and prevents pesticide leakage. Abstract : The development of new approaches for pesticide delivery is a most relevant subject in the area of crop protection, which typically involves relatively high pesticide dosing combined with low deposition and limited biosafety. Herein, we investigate a pesticide carrier system based on plant-derived, eco-friendly cellulose nanocrystals (CNCs) modified with β-cyclodextrin (β-CD) and tannic acid (TA). A broad-spectrum and widely used pesticide, fenitrothion (XCM), was shown to bind to the carrier through hydrophobic and hydrogen bonding interactions and Cu 2+ coordination, enabling pH-controlled delivery. The high axial aspect of CNCs and surface features endowed by β-CD binding facilitated contact and enhanced the deposition efficiency on the foliage. The tannic acid further improved wetting, adhesion and retention on leaves (1.8-fold higher than TA-free systems). The bioactivity tests showed efficient antifungal (74%) and insecticidal (97%) effects along with excellent biosafety, highlighting the introduced carrier for its promise in the area of pesticide delivery.